Comparison of bone age in small-for-gestationalage children vs appropriate-for-getational-age children - Lionardus Edward; Sjarif Hidajat Effendi; Djatnika Setiabudi (Indonesian Pediatric Society, 2010)
BackgroundAbout 10-15% small-for-gestational-age children are in higher risk for having linear growth retardation due to growth hormone-insulin like growth factor 1 axis defect (GH-IGF 1) which causes bone age delay.ObjectivesTo compare bone age in 24-36 month old children born small-for-gestational-age (SGA) to that in children born appropriate-for-gestational-age (AGA).MethodsA cross-sectional study was conducted in Hasan Sadikin General Hospital, Bandung, from January to April 2009.Subjects consisted of50 healthy children of 24-36 months old (25 children born at term, SGA, 25 children born at term, AGA). We compared the appropriateness and delay of bone age between the two groups. ResultsMean bone age in the SGA group was 20.8 (SD 7.7) months, and in the AGA group was 25.7 (SD 7.1) months (P=0.022). Mean bone age deficit was -10.5 (6.5) months in the SGA group and -5.5 (SD 5.7) months in the AGA group (P=0.009). The prevalence ratio was 1.77 (95% CI: 1.19–2.62). Bone age delay was found to be higher in children born SGA than that in children of the other group (23 vs 13). On the contrary, appropriate bone age was found more in children born AGA (12 vs 2) (P=0.002).Conclusion Bone age delay in 24-36 months old children born small-for-gestational-age was found to be higher than in those born appropriate-for-gestational-age.